Physiological factors affecting the mechanical performance of peripheral muscles: A perspective for long COVID patients through a systematic literature review - Suba Rao, Harinivas Rao; Hamzaid, Nur Azah; Ahmad, Mohd Yazed; Hamzah, Norhamizan (Frontiers in Physiology, 2022)
BACKGROUND: Long COVID patients experience peripheral muscle weakness that can be measured quantitatively. Mechanomyography (MMG) is an alternative tool to measure muscle strength non-invasively. OBJECTIVE: This literature search focuses on the physiological parameters that could influence MMG readings of peripheral muscle strength in long COVID patients. METHODS: A systematic literature review was conducted on Web of Science and Scopus databases. A total of 5 studies out of 17 publications satisfied the inclusion criteria. RESULTS: The studies that addressed muscle performance reported the physiological effects of age, gender, and physical activity level. In terms of assessment, it is worth noting that hand grip strength is not recommended as a proxy for overall muscular strength. Lower body muscle strength such as knee augmentation strength should be measured as part of geriatric evaluations, and more currently, for post COVID evaluations. CONCLUSIONS: MMG parameters during rest presently have inter-consultation and inter-day reliability and sensitivity. The consequences of tiredness and the time it takes to recover may affect the correlations between torque and mechanomyogram. Sensors like MMG, as well as the length of the muscle and the characteristics of the muscle activity, are important considerations when choosing a sensor for a particular diagnostic evaluation.